Environmental factors, human presence and prey interact to explain patterns of tiger presence in Eastern Thailand - Ash, E; Kaszta, Ż; Noochdumrong, A; Redford, T; David MACDONALD (Wiley, 2020)
Thailand is one of the last strongholds for tigers Panthera tigris in mainland Southeast Asia. Evidence suggests heterogeneity in tiger presence in a globally important landscape in Eastern Thailand is potentially influenced by a complex interaction of prey, human presence and environmental conditions. Understanding these dynamics is of considerable importance for the conservation of tigers both in this landscape and elsewhere in their range. In this study, we examine which factors, among prey, human presence and environmental characteristics, best explain tiger presence in the Dong Phayayen–Khao Yai Forest Complex (DPKY). We collated survey data from 56,214 camera trap nights and evaluated the relationship between tiger presence and a suite of five prey, 11 human presence and eight environmental variables. We then used variance partitioning to discern the degree of variance in tiger presence explained by these factors. We documented strong, positive associations with wild boar Sus scrofa presence and prey richness, and strong, negative associations with human settlement density, public roads and presence of poachers. Environmental characteristics explained a greater relative proportion of variance (19.6%) in tiger presence than prey covariates alone (3.1%), particularly confounded with human presence (31.1%). This suggests that environmental variables, especially when accompanied by anthropogenic factors, could be used to model potential tiger occurrence where other data may be lacking. Our approach may be helpful in providing guidance for prioritizing habitat, evaluating the effect of human presence and identifying key prey to provide a foundation for tiger protection and recovery.